Clinical features and long‐term outcomes of 105 granulomatosis with polyangiitis patients: A single center experience from north India. (24th March 2017) - Sharma, Aman; Naidu, Godasi S. R. S. N. K.; Rathi, Manish; Verma, Roshan; Modi, Manish; Pinto, Benzeeta; Sharma, Kusum; Dhir, Varun; Singhal, Manphool; Prakash, Mahesh; Nada, Ritambhra; Panda, Naresh K.; et al.
Abstract: Aim: To describe the clinical features, treatment and long‐term outcomes in north Indian patients with granulomatosis with polyangiitis (GPA). Methods: Clinical details, Birmingham Vasculitis Activity Score (BVAS‐v3), laboratory data, histopathology findings, treatment details and outcomes of all consecutive patients diagnosed as having GPA between April 2005 and April 2016 were retrieved. European Vasculitis Study Group definitions were used to classify patients into localized, early systemic, generalized, severe and refractory categories. The findings were compared with large single center cohorts from USA, Germany and France. Results: One hundred and five patients (median age 40 years; 60 females and 45 males) were diagnosed as having GPA. Median duration of follow up was 28 months. Upper respiratory tract, renal and lung involvement were seen in 76.19%, 51.43% and 67.62% of patients, respectively. Ocular, ear, central nervous system, peripheral nervous system, heart, gastrointestinal and skin involvement were seen in 40.95%, 18.1%, 26.67%, 11.43%, 5.71%, 12.38% and 29.52%, respectively. The median BVAS v3 score was 17. Localized, early systemic, generalized, severe and refractory disease were seen in three, 44, 38, 17 and one patient, respectively. Eighteen patients expired and the cause of death was disease activity in 11, disease activity plus sepsis in four and sepsis alone in three patients. Twenty‐six patients experienced relapses. No hemorrhagic cystitis or bladder cancers were observed; however, one patient developed myelodysplastic syndrome during follow up. Conclusion: Indian patients are younger and have less arthritis, renal and peripheral nerve involvement as compared to the patients in Western cohorts.